Nilai Dan Norma Sosial Dalam Peristiwa Al-Ifk Pada Qs Al-Nūr: Analisis Tafsir Tematik Dan Relevansinya Bagi Pendidikan Karakter - Lailatul Hikmah; Muhammad Tareh Aziz; Moh. Syafi’i (DAARUS TSAQOFAH Jurnal Pendidikan Pascasarjana Universitas Qomaruddin, 2026)
The al-Ifk incident is not merely a historical record of slander within the Prophet's household, but also contains a framework of social ethics relevant to communal life, including in the context of character education and values education. Previous studies have generally discussed the value of tabayyun separately in relation to QS al-Ḥujurāt verse 6, or examined the al-Ifk incident only from its narrative-historical aspect, such that few have comprehensively linked the narrative, epistemic-ethical (husnuzhan-tabayyun), and legal (had qadzf) dimensions of the al-Ifk incident with the framework of Character Education Strengthening (Penguatan Pendidikan Karakter/PPK). This article seeks to fill that gap by employing the thematic exegesis method (mawḍū‘ī), grounded in library research on classical exegetical works (Ibn Kathīr, al-Qurṭubī, al-Ṭabarī, al-Shawkānī) and contemporary ones (Tafsir al-Mishbah), as well as supporting literature from indexed journal articles. The discussion focuses on three main points: (1) the narrative construction and socio-historical context of the al-Ifk incident; (2) husnuzhan (positive assumption) and tabayyun (clarification/verification) as the foundation of epistemic-social ethics in communication; and (3) the legal norm of had qadzf and the community's collective responsibility in safeguarding honor (‘ird), along with its relevance to character education. The findings indicate that the social norms embedded in the al-Ifk incident form a mutually reinforcing system of communication ethics encompassing the affective dimension (husnuzhan), the procedural dimension (tabayyun), and the legal dimension (had qadzf), which together can serve as a reference for character education in cultivating information literacy, verbal self-restraint, and social responsibility among learners amid the current surge of information and disinformation. This article recommends that these values be explicitly integrated into the Islamic religious education curriculum as well as into Character Education Strengthening programs at educational institutions.